PERBANDINGAN KUALITAS BAHAN BAKAR DARI PENGOLAHAN SAMPAH PLASTIK MENJADI BAHAN BAKAR MINYAK DENGAN METODE PIROLISIS - Mariaulfa Mustam; Nurfika Ramdani; Irfan Syaputra (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2021)
Given the existence of plastic waste in the environment is very dangerous, therefore it is necessary to conduct research to handle it. The development of technology for plastic processing to produce something useful continues to be carried out by various groups, ranging from scientists, academics, and students. One of them is the utilization of plastic waste into fuel oil (BBM) using the pyrolysis technique which will be installed to process plastic waste. The purpose of this study was to determine the fuel oil from processing plastic waste and compare the fuel with kerosene and diesel oil with the parameters of density, burning time and water temperature when heating using the three fuel oils. The research method used is data collection techniques including pre-treatment, the process to determine the density of each fuel sample, the process of burning time, temperature during heating, analysis of the density of pyrolysis oil, kerosene and diesel fuel by measuring the volume and the mass of each sample. Comparison of the quality of Fuel Burning Time, namely Oil from recycled plastics 4.01 minutes, Diesel Oil 4.45 minutes, and Kerosene 3.02 minutes. Comparison of the quality of water temperature with a volume of 20 ml of water and a heating time of 5 minutes, it is found that recycled plastic oil is 0.77oC, diesel oil is 0.73oC, kerosene is 0.84oC. plastic waste processing is under kerosene but above diesel oil based on density indicators, burning time, water temperature when heating.